Contemporaneous comparison of open vs minimally‐invasive radical prostatectomy for high‐risk prostate cancer - Pierorazio, Phillip M.; Mullins, Jeffrey K.; Eifler, John B.; Voth, Kipp; Hyams, Elias S.; Han, Misop; Pavlovich, Christian P.; Bivalacqua, Trinity J.; Partin, Alan W.; Allaf, Mohamad E.; Schaeffer, Edward M. (BJU international, 2013)
What's known on the subject? and What does the study add? The ideal treatment for men with high‐risk prostate cancer is controversial, although most physicians agree that a multimodal approach, including radiation and hormone therapy with or without surgery, offers the best chance of cancer control. Minimally‐invasive radical prostatectomy has emerged as a treatment option for clinically localized cancer; however, critics argue that the open approach may afford advantages of tactile feedback and a better lymph node dissection. The present study demonstrates that open and minimally‐invasive radical prostatectomy offer equivalent short‐term outcomes for men with high‐risk prostate cancer at a highly experienced centre. Objectives To analyze pathological and short‐term oncological outcomes in men undergoing open and minimally‐invasive radical prostatectomy (MIRP) for high‐risk prostate cancer (HRPC; prostate‐specific antigen level [PSA] >20 ng/mL, ≥ cT2c, Gleason score 8–10) in a contemporaneous series. Patients and Methods In total, 913 patients with HRPC were identified in the Johns Hopkins Radical Prostatectomy Database subsequent to the inception of MIRP at this institution (2002–2011) Of these, 743 (81.4%) underwent open radical retropubic prostatectomy (ORRP), 105 (11.5%) underwent robot‐assisted laparoscopic radical prostatectomy (RALRP) and 65 (7.1%) underwent laparoscopic radical prostatectomy (LRP) for HRPC. Appropriate comparative tests were used to evaluate patient and prostate cancer characteristics. Proportional hazards regression models were used to predict biochemical recurrence. Results Age, race, body mass index, preoperative PSA level, clinical stage, number of positive cores and Gleason score at final pathology were similar between ORRP and MIRP. On average, men undergoing MIRP had smaller prostates and more organ‐confined (pT2) disease (P = 0.02). The number of surgeons and surgeon experience were greatest for the ORRP cohort. Overall surgical margin rate was 29.4%, 34.3% and 27.7% (P = 0.52) and 1.9%, 2.9% and 6.2% (P = 0.39) for pT2 disease in men undergoing ORRP, RALRP and LRP, respectively. Biochemical recurrence‐free survival among ORRP, RALRP and LRP was 56.3%, 67.8% and 41.1%, respectively, at 3 years (P = 0.6) and the approach employed did not predict biochemical recurrence in regression models. Conclusions At an experienced centre, MIRP is comparable to open radical prostatectomy for HRPC with respect to surgical margin status and biochemical recurrence.